The effect of yoghurt and its probiotics on blood pressure and serum lipid profile; a randomised controlled trial - Ivey, K.; Hodgson, J.; Kerr, Deborah; Thompson, P.; Stojceski, B.; Prince, R. (Elsevier, 2015)
Background and aims: Despite strong mechanistic data, and promising results from in vitro and animal studies, the ability of probiotic bacteria to improve blood pressure and serum lipid concentrations in humans remains uncertain. The aim of this study was to determine the effect of Lactobacillus acidophilus La5 and Bifidobacterium animalis subsp lactis Bb12, provided in either yoghurt or capsule form, on home blood pressure and serum lipid profile. Methods and results:Following a 3-week washout period, 156 overweight men and women over 55 y were randomized to a 6-week double-blinded, factorial, parallel study. The four intervention groups were: A) probiotic yoghurt plus probiotic capsules; B) probiotic yoghurt plus placebo capsules; C) control milk plus probiotic capsules; and D) control milk plus placebo capsules. Each probiotic test article provided a minimum L. acidophilus La5 and B. animalis subsp. lactis Bb12 dose of 3.0 × 109 CFU/d. Home blood pressure monitoring, consisting of 7-day bi-daily repeat measurements, were collected at baseline and week 6. Fasting total cholesterol, low density lipoprotein cholesterol (LDLC), high density lipoprotein cholesterol (HDLC), and serum triglyceride were performed at baseline and week 6. When compared to control milk, probiotic yoghurt did not significantly alter blood pressure, heart rate or serum lipid concentrations (P > 0.05). Similarly, when compared to placebo capsules, supplementation with probiotic capsules did not alter blood pressure or concentrations of total cholesterol LDLC, HDLC, or triglycerides (P > 0.05). Conclusions: The probiotic strains L. acidophilus La5 and B. animalis subsp. lactis Bb12 did not improve cardiovascular risk factors.